2021
DOI: 10.2147/jmdh.s308397
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patterns of Turnover Intention Among Alabama Frontline Nurses in Hospital Settings During the COVID-19 Pandemic

Abstract: Introduction: Current research about frontline nurse stress and turnover intention lacks context related to rural communities' plight in providing organizational resources during the current COVID-19 pandemic. These implications have been particularly underexamined in the United States, whose regional differences may influence how frontline nurses perceive the access and utility of organizational resources. This study investigates if anxiety and stress while working during the current COVID-19 pandemic contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 60 publications
5
72
3
4
Order By: Relevance
“…The literature on healthcare workers indicates that lack of perceived organizational support is among the several factors that enhance turnover intention and other negative behaviors [37,38]. Previous studies also claim that fear caused by the contagious disease can be reduced when healthcare workers are confident that hospital management prioritizes their safety [22]. In short, the perception of hospital measures against COVID-19 can be an important resource to help employees safeguard their resources.…”
Section: Moderating Role Of Perception Of Hospital Measures Against Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on healthcare workers indicates that lack of perceived organizational support is among the several factors that enhance turnover intention and other negative behaviors [37,38]. Previous studies also claim that fear caused by the contagious disease can be reduced when healthcare workers are confident that hospital management prioritizes their safety [22]. In short, the perception of hospital measures against COVID-19 can be an important resource to help employees safeguard their resources.…”
Section: Moderating Role Of Perception Of Hospital Measures Against Covid-19mentioning
confidence: 99%
“…The lack of available treatment for COVID-19 could be a concrete cause of healthcare workers' turnover. Employee perceptions about the measures taken against the disease, act as a deciding factor for quitting the job [22]. Existing studies have shown that healthcare workers are more likely to stay and provide treatment for infectious diseases if they perceive that the hospital has taken sufficient measures to ensure their protection [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] Their heavy workloads affect their ability to cope with the demands of their work and to derive a sense of fulfillment from ensuring patients' safety and providing people with high-quality care. [14][15][16][17] The responsibility of healthcare providers is to directly provide and manage COVID-19 care processes, 18,19 which, considering the overwhelming number of cases, may cause them to develop mental health issues and fail to perceive their own psychological distress symptoms such as anxiety or depression. 20,21 The perspectives of healthcare providers experiencing burnout during the current pandemic should thus be obtained to gain a better understanding of how they are handling such situation and to help them resolve their issues.…”
Section: Introductionmentioning
confidence: 99%
“…Cronbach's alpha statistics were above 0.60 for each construct which satisfies the minimum threshold of 0.60 (Mohamad, Sulaiman, Sern, & Salleh, 2015) indicating that the constructs are reliable. Also, several sociodemographic characters that may be influential on employee turnover during the Covid-19 pandemic such as gender and age were considered as control variables (Bajrami, et al, 2021;Cole, Ali, Ahmed, Hamasha, & Jordan, 2021). The questionnaire was first developed in English and translated to the local (Sinhala) language.…”
Section: Sample and Data Collectionmentioning
confidence: 99%